A Novel Fusion Protein System for the Production of Nanobodies and the SARS-CoV-2 Spike RBD in a Bacterial System - Dóra Nagy-Fazekas; Pál Stráner; Péter Ecsédi; Nóra Taricska; Adina Borbély; László Nyitray; András Perczel (Bioengineering, 2023)
Antibodies are key proteins of the immune system, and they are widely used for both research and theragnostic applications. Among them, camelid immunoglobulins (IgG) differ from the canonical human IgG molecules, as their light chains are completely missing; thus, they have only variable domains on their heavy chains (VHHs). A single VHH domain, often called a nanobody, has favorable structural, biophysical, and functional features compared to canonical antibodies. Therefore, robust and efficient production protocols relying on recombinant technologies are in high demand. Here, by utilizing ecotin, an Escherichia coli protein, as a fusion partner, we present a bacterial expression system that allows an easy, fast, and cost-effective way to prepare nanobodies. Ecotin was used here as a periplasmic translocator and a passive refolding chaperone, which allowed us to reach high-yield production of nanobodies. We also present a new, easily applicable prokaryotic expression and purification method of the receptor-binding domain (RBD) of the SARS-CoV-2 S protein for interaction assays. We demonstrate using ECD spectroscopy that the bacterially produced RBD is well-folded. The bacterially produced nanobody was shown to bind strongly to the recombinant RBD, with a Kd of 10 nM. The simple methods presented here could facilitate rapid interaction measurements in the event of the appearance of additional SARS-CoV-2 variants.